Avoidant conversations about death by clinicians cause delays in reporting of neutropenic sepsis: Grounded theory study. Issue 10 (19th December 2016) - Oakley, Catherine; Taylor, Cath; Ream, Emma; Metcalfe, Alison
Abstract: Background: Evidence suggests that patients delay reporting symptoms of neutropenic sepsis (NS) despite the risk to their life. This study aimed to elicit factors that contribute to delayed patient reporting of NS symptoms. Methods: A constructivist grounded theory study used observations of chemotherapy consultations (13 h) and 31 in‐depth interviews to explore beliefs, experiences, and behaviors related to NS. Participants included women with breast cancer, their carers (partners, family, or friends), and clinicians. An explanation for patient delays was developed through theoretical sampling of participants to explore emerging areas of interest and through constant comparison of data and their coding. This entailed iterative and concurrent data collection and analysis. Data were collected until saturation. Results: All patients who developed NS‐type symptoms delayed presenting to hospital (2.5 h‐8 days), sometimes repeatedly. Moderators of delay included metastatic disease, bereavement, fatalism, religious beliefs, and quality of relationships with clinicians. There was an interplay of behaviors between clinicians, patients, and carers where they subconsciously conspired to underplay the seriousness and possibility of NS occurring. Conclusions: Findings have implications for health risk communication and development of holistic service models.